1999
DOI: 10.1152/ajpcell.1999.277.4.c665
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide triggers intracellular calcium release via the IP3 receptor inXenopus laevisoocytes

Abstract: Ceramide, a product of sphingomyelin turnover, is a lipid second messenger that mediates diverse signaling pathways, including those leading to cell cycle arrest and differentiation. The mechanism(s) by which ceramide signals downstream events have not been fully elucidated. Here we show that, in Xenopus laevis oocytes, ceramide-induced maturation is associated with the release of intracellular calcium stores. Ceramide caused a dose-dependent elevation in the second messenger inositol 1,4,5-trisphosphate (IP3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(21 citation statements)
references
References 54 publications
1
19
0
1
Order By: Relevance
“…Furthermore, ceramide addition to Xenopus oocytes released [Ca 21 ] in through Gq, PLCb, and IP3 receptor activation (83). Because this G protein pathway is not thought to be involved in [Ca 21 ] in release as initiated by sperm (84), ceramide may not play a role in the calcium release at fertilization.…”
Section: Sm and Ceramidementioning
confidence: 99%
“…Furthermore, ceramide addition to Xenopus oocytes released [Ca 21 ] in through Gq, PLCb, and IP3 receptor activation (83). Because this G protein pathway is not thought to be involved in [Ca 21 ] in release as initiated by sperm (84), ceramide may not play a role in the calcium release at fertilization.…”
Section: Sm and Ceramidementioning
confidence: 99%
“…In our studies we used human recombinant TNF␣, which in rodent cells activates the p55 TNF␣ receptor and signaling pathways that generate ceramide (42,43); ceramide has been shown to trigger intracellular calcium release through IP 3 receptors (44). It appears that one factor controlling the cell susceptibility to ceramide-induced apoptosis is the [Ca 2ϩ ] er (39).…”
Section: Inhibition Of Ip 3 -Induced Calcium Release Protects Relamentioning
confidence: 99%
“…To account for this function, observations in model and cell membranes reported the flipflop movement of ceramide (42,43), gaining access to the inner leaflet of the plasma membrane to interact with specific targets. In agreement with this concept, extracellular NSMase from S. aureus has been shown to increase cytoplasmic Ca 21 via the inositol-3-phosphate receptor Ca 21 release channel on the endoplasmic reticulum, leading to oocyte maturation (51). Moreover, another study reported that the inhibition of glycosphingolipid synthesis by 1-phenyl-2-decanoylamino-3-morpholino-1-propanol (PDMP), an inhibitor of the glucosylceramide synthase (GCS) (52), activated p34 cdc2 in Xenopus oocytes and induced GVBD and maturation (45).…”
Section: Discussionmentioning
confidence: 62%